Paleoceanographic development in Storfjorden, Svalbard, during the deglaciation and Holocene: evidence from benthic foraminiferal records - Rasmussen, Tine Lander; Thomsen, Erik (Boreas, 2014)
This is the peer reviewed version of the following article: Rasmussen, T.L. & Thomsen, E. (2015). Paleoceanographic development in Storfjorden, Svalbard, during the deglaciation and Holocene: evidence from benthic foraminiferal records. Boreas, 44(1), 24-44. https://doi.org/10.1111/bor.12098, which has been published in final form at https://doi.org/10.1111/bor.12098 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Brines can have a profound influence on the relative abundance of calcareous and agglutinated foraminiferal faunas. Here we investigated the distribution of benthic foraminiferal species in four cores from a brine‐enriched environment in Storfjorden, Svalbard. Stratigraphically, the cores comprise the last 15 000 years. The purpose of the study was to reconstruct changes in the palaeoecology and palaeoceanography of Storfjorden in relation to past climate changes, and to identify potential indicator species for brine‐affected environments. The benthic foraminifera in Storfjorden all have widespread occurrences in the Arctic realm. Calcareous species dominated Storfjorden during the deglaciation and early Holocene until c. 8200 a BP. However, agglutinated species increased in abundance whenever conditions became colder with more sea ice and stronger brine formation, such as during the Older Dryas, the Intra‐Allerød Cold Period and the Younger Dryas. Following a moderately cold period with numerous agglutinated foraminifera from c. 8200–4000 a BP, conditions became more changeable from c. 4000 a BP with repeated shifts between warmer periods dominated by calcareous species and colder periods dominated by agglutinated species. The warmer periods show a stronger influence of Atlantic Water, with reduced brine formation and less corrosive conditions at the sea bottom. Conversely, the colder periods show a stronger influence of Arctic water, with higher brine production and more corrosive bottom water. The ...